2013
DOI: 10.3389/fpls.2013.00308
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphate levels strongly influence ascorbate and starch content in tomato fruit

Abstract: Ascorbate (vitamin C) deficiency leads to low immunity, scurvy, and other human diseases and is therefore a global health problem. Given that plants are major ascorbate sources for humans, biofortification of this vitamin in our foodstuffs is of considerable importance. Ascorbate is synthetized by a number of alternative pathways: (i) from the glycolytic intermediates D-glucose-6P (the key intermediates are GDP-D-mannose and L-galactose), (ii) from the breakdown of the cell wall polymer pectin which uses the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 101 publications
1
12
0
Order By: Relevance
“…For example, the expression of an Escherichia coli cytosolic inorganic pyrophosphatase gene in tobacco and potato significantly increased the ratio between soluble sugars and starch; which alters the photoassimilate partitioning (Sonnewald, 1992). Recently, Osorio et al (2013) demonstrated that overexpression of the gene encoding the inorganic pyrophosphatase from E. coli in transgenic tomato, increases the levels of major sugars (sucrose and glucose) and decreases the level of starch in ripe fruit. Interestingly, the ectopic expression of the E. coli pyrophosphatase gene also resulted in increased vitamin C levels up to 2.5-fold.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the expression of an Escherichia coli cytosolic inorganic pyrophosphatase gene in tobacco and potato significantly increased the ratio between soluble sugars and starch; which alters the photoassimilate partitioning (Sonnewald, 1992). Recently, Osorio et al (2013) demonstrated that overexpression of the gene encoding the inorganic pyrophosphatase from E. coli in transgenic tomato, increases the levels of major sugars (sucrose and glucose) and decreases the level of starch in ripe fruit. Interestingly, the ectopic expression of the E. coli pyrophosphatase gene also resulted in increased vitamin C levels up to 2.5-fold.…”
Section: Discussionmentioning
confidence: 97%
“…Ectopic starch grain formation occurred in fugu5-1 ppa1-1 ( Figure 10). The relationship between starch and PPi was previously examined by overexpressing sPPase in plants (Sonnewald, 1992;Lerchl et al, 1995;Geigenberger et al, 1998;Meyer et al, 2012;Osorio et al, 2013); however, the starch contents in transgenic plants generated in these studies varied. Theoretically, overexpressing sPPase should reduce starch biosynthesis and increase soluble sugar content due to a decrease in PPi and glucose 6-phosphate (Glc-6P) levels.…”
Section: Starch Accumulates In Source and Sink Organs In Response To mentioning
confidence: 99%
“…VITAMIN C DEFECTIVE1 (VTC1)/CYTOKINESIS DEFECTIVE1 (CYT1; hereafter, VTC1 indicates VTC1/CYT1 protein) has been identified as the major form of GMPP in Arabidopsis, and evidence for its key role in AsA synthesis comes from a number of different studies: In Arabidopsis thaliana, the vtc1-1 mutant, a leaky mutant for the VTC1 gene, exhibits a 70% decrease in AsA level (Conklin et al, 1997(Conklin et al, , 1999) and a CONSTITUTIVE PHO-TOMORPHOGENESIS9 (COP9) signalosome subunit, CSN5B, downregulates AsA level through the degradation of VTC1 in the dark (Wang et al, 2013b). In tomato (Solanum lycopersicum), metabolic engineering to increase pyrophosphate (PPi) levels substantially decreased AsA quantity, as it promoted pyrophosphorolysis of GDP-Man into Man 1-P and GTP by GMPP (Osorio et al, 2013). Due to the pivotal role of this enzyme, efforts to enhance AsA levels in planta have targeted VTC1 gene expression (Cronje et al, 2012).…”
Section: Introductionmentioning
confidence: 99%